Design of cinnamaldehyde- and gentamicin-loaded double-layer corneal nanofiber patches with antibiofilm and antimicrobial effects - CESUR, SÜMEYYE (My University, 2023)
: In this study, two-layer poly(vinyl alcohol)/gelatin (PVA/GEL) nanofiber patches containing cinnamaldehyde (CA) in the first layer and gentamicin (GEN) in the second layer were produced by the electrospinning method. The morphology, chemical structures, and thermal temperatures of the produced pure (PVA/GEL), CA-loaded (PVA/ GEL/CA), GEN-loaded (PVA/GEL/GEN), and combined drug-loaded (PVA/GEL/CA/ GEN) nanofiber patches were determined by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy, and differential scanning calorimetry, respectively. Their mechanical properties, swelling and degradation behavior, and drug release kinetics were investigated. SEM images showed that both drug-free and drug-loaded nanofiber patches possess smooth and monodisperse structures, and nanofiber size increase occurred as the amount of drug increased. The tensile test results showed that the mechanical strength decreased as the drug was loaded. According to the drug release results, CA release ended at the 96th hour, while GEN release continued until the 264th hour. The antibacterial and antibiofilm activities of PVA/GEL, PVA/GEL/CA, PVA/GEL/GEN, and PVA/GEL/CA/GEN nanofiber patches against Pseudomonas aeruginosa and Staphylococcus aureus were evaluated. Results showed that PVA/GEL/GEN and PVA/GEL/CA/GEN nanofiber patches have excellent antibacterial and antibiofilm activities. Moreover, all materials were biocompatible, with no cytotoxic effects in the mammalian cell model for 8 days. PVA/GEL/GEN nanofiber patches were the most promising material for a high cell survival ratio, which was confirmed by SEM images. This research aims to develop an alternative method to stop and treat the rapid progression of bacterial keratitis.
Keywords: Absorption; Antimicrobial agents; Biofilms; Drug release; Nanofibers